Ação de Polistes (Aphanilopterus) simillimus Zikán (Hymenoptera, Vespidae) no controle de Spodoptera frugiperda (Smith) (Lepidoptera, Noctuidae) - Prezoto, Fábio; Machado, Vera L.L [UNESP] (Sociedade Brasileira de Zoologia, 1999)
The corn is a plantation attacked by a lot of pests, mainly by Caterpillar Spodoptera frugiperda (Smith), producing serious damages in the plants, occasioning unproductiveness. Thus, the goal of this research was to verify the predation of Polistes simillimus (Zikán, 1951) wasps on this pest of a corn plantation using the wasps colonies as a efficient form of this pest management. The present research was developed in a area in the Piracicaba county, São Paulo (22º43'S, 47º38'W), during the period of november/1995-march/1996, introducing 20 P. simillimus colonies in artificial wood shelters around of 5 plots of com, to accompany the foraging activity of the wasps and the development of the wasps colonies. Spodoptera frugiperda (23,07%) was the main prey captured by the wasps and the average rate of capture was 1,54 preys/h. These data gave an estimation of reduction in the occurrence of S. frugiperda (77,16%), due mainly to the wasps action.
Action of Polistes (Aphanilopterus) simillimus Zikán (Hymenoptera, Vespidae) in the control of Spodoptera frugiperda (Smith) (Lepidoptera, Noctuidae)
Keywords: Biology control; corn plantation; pests and predators